Health benefits of joint replacement surgery for patients with osteoarthritis: prospective evaluation using independent assessments in Scotland. Issue 9 (September 1998) - Orbell, S; Espley, A; Johnston, M; Rowley, D
Abstract : STUDY OBJECTIVES: To determine extent of change in psychological, functional, and social health after knee and hip joint replacement surgery using independent assessments. DESIGN: Patients were recruited before surgery and interviewed preoperatively, three months after surgery, and nine months after surgery. Interviews were conducted in the patients' own homes. SETTING: Two orthopaedic surgery units in Scotland. PARTICIPANTS: A consecutive sample of 107 patients with osteoarthritis having primary replacement of the knee or hip. MAIN OUTCOME MEASURES: Assessments of depression, anxiety, pain, functional activity, informal care, and formal service utilisation were made at three time points. MAIN RESULTS: Anxiety and pain were significantly reduced and functional activity levels significantly increased after surgery. While gains in anxiety and pain reduction occurred between the preoperative and three month assessments, gains in activity were made between the three month and nine month assessments. Although pain was reduced and activity increased, levels of depression were unchanged after surgery. Patients reported need for assistance with fewer activities after surgery, but increases in the use of formal services and increases in the number of hours per week of informal support received were observed at both three month and nine month follow up. CONCLUSIONS: The main benefit of joint replacement surgery is pain relief. Gains in functional activity, particularly mobility and leisure activities are made by many patients. Paradoxically, surgery for osteoarthritis seems to act as a "gateway" to increases in formal and informal community support, which are maintained into the longer term.